The role of values in coping with health and economic threats of COVID-19 - Lemay Jr., Edward P; Kruglanski, Arie W; Molinario, Erica; Agostini, Maximilian; Belanger, Jocelyn J; Gutzkow, Ben; Kreienkamp, Jannis; Reitsema, Anne Margit; vanDellen, Michelle R; PsyCorona, Collaboration; Abdul Khaiyom, Jamilah Hanum; Leander, N Pontus (Taylor & Francis Online, 2021)
The current research examined the role of values in guiding people’s responses to COVID-19. Results from an international study involving 115 countries (N = 61,490) suggest that health and economic threats of COVID-19 evoke different values, with implications for controlling and coping with the pandemic. Specifically, health threats predicted prioritization of communal values related to caring for others and belonging, whereas economic threats predicted prioritization of agentic values focused on competition and achievement. Concurrently and over time, prioritizing communal values over agentic values was associated with enactment of prevention behaviors that reduce virus transmission, motivations to help others suffering from the pandemic, and positive attitudes toward outgroup members. These results, which were generally consistent across individual and national levels of analysis, suggest that COVID-19 threats may indirectly shape important responses to the pandemic through their influence on people’s prioritization of communion and agency. Theoretical and practical implications are discussed.